Performance Analysis of Intelligent Reflecting Surface-Assisted Wireless System With Non-Ideal Transceiver - Mohd Hamza Naim Shaikh; Vivek Ashok Bohara; Anand Srivastava; Gourab Ghatak (IEEE Open Journal of the Communications Society)
Intelligent Reflecting Surfaces (IRSs) have recently emerged as a promising solution for realizing the smart radio environment concept by leveraging the characteristics of metamaterials and large antenna arrays. However, the existing works on IRS do not account for the transceiver impairments while analyzing the performance of IRS assisted wireless systems. This paper investigates the impact of transceiver hardware imperfections on the performance of IRS-assisted wireless systems. Specifically, we have analyzed the spectral efficiency (SE), the energy efficiency (EE) and the outage probability of IRS-assisted wireless systems by deriving their closed-form expressions and verifying them through simulation results. The results show the importance of modeling and compensating for hardware impairment as they significantly restrict the performance of such systems.